Reflections on writing and teaching: a study of five writing contest winners. Issue 3 (12th August 2021) - Williams, Wendy R.
Abstract : Purpose: English teachers who write have valuable expertise that can benefit students. Although there is a fair amount of research on teacher-writers, little is known about teachers' writing lives outside of educational or professional contexts. This paper aims to investigate the writing lives and teaching beliefs of five writing contest winners. Design/methodology/approach: This qualitative study, which was guided by sociocultural theory and concepts such as literacy sponsorship, involved individual semi-structured interviews, questionnaires and writing and teaching artifacts. Findings: Data analysis resulted in several themes describing participants' writing lives: Writing Experiences, Writing Practices and Writing Attitudes. In addition, several themes emerged describing their teaching beliefs: Writing Assignments/Tools, Modeling and Credibility/Empathy/Vulnerability. Overlaps exist in the descriptions of their writing and teaching lives. Practical implications: Teachers' writing lives are valuable resources for instruction. It is recommended that teachers have opportunities to reflect on who they are as writers and what has shaped them. Teachers also need new experiences to expand their writing practices and strengthen their writing identities alongside fellow writers. More must be done to understand, nurture and sustain teachers' writing. Originality/value: This research expands the conversation on teachers as writers by involving writing contest winners, focusing on their writing lives and noticing how their writing experiences, practices and attitudes inform their teaching. This study suggests several ways to move forward in supporting teachers as writers, keeping in mind the social aspects of learning.